Assessing the burden and spatial distribution of Taenia solium human neurocysticercosis in Ecuador (2013-2017). - Marco Coral-Almeida; Aquiles R Henriquez-Trujillo; Sofia Asanza; Celia Erazo; Michelle Paucar; Manuel Calvopiña (Public Library of Science (PLoS), 2020)
Background Estimating the burden of neglected tropical diseases is a valuable tool to support policymakers in the resource allocation for control and elimination of these diseases. Spatial analysis allows to identify the geographical distribution patterns of infectious and parasitic diseases within a country and allows to assess their possible correlation with other health disorders. Despite being neurocysticercosis (NCC) considered as the most important parasitic disease of the nervous system, few efforts have been addressed to assess the real burden of NCC in endemic countries, to date, there are no studies estimating the burden of NCC in South America. In this study we aimed to use the Disability Adjust Life Years (DALY) and spatial indicators as tools to measure the impact of human neurocysticercosis in Ecuador between 2013 and 2017. Methods Mortality, morbidity and spatial data from the national agency of statistics were used to estimate the burden of disease of NCC during a five-year period (2013-2017). NCC cases and its two main sequelae, epilepsy and migraine headache, were stratified by sex and age group to calculate the DALY associated to NCC using the DALY package in R. SATSCAN software was used to assess spatial clusters of NCC and its possible neurological sequelae as epilepsy, status epilepticus, migraine and hydrocephalus. Principal findings The burden of human neurocysticercosis ranged from 56201 [95% CI 29961-89333] to 59612 [95% CI 31854-94689] DALY per year, corresponding to 3.54 to 3.56 DALY per 1000 population. Average yearly incidence rates per 10 000 person-years were 0.23 [95% CI 0.21-0.26] for NCC, 4.89 [95% CI 4.78-5.00] for epilepsy, 0.130 [95% CI 0.11-0.15] for status epilepticus, 0.62 [95% CI 0.58-0.66] for migraine headache, and 1.02 [95% CI 0.98-1.07] for hydrocephalus. Most important significant spatial clusters (p<0.0001) were located in the southern region of the highlands of the country. Conclusion/significance This is the first study in South America to calculate estimates for burden of NCC and one of the few using spatial analysis to show the importance of sequelae other than epilepsy that play an important role in the impact of human neurocysticercosis.